Early Childhood Education and Its Correlation with Crime: A Review - Anwar Anwar; Tatum Derin (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2019)
This article reviews the new evidence offered by Jorge Luis García, James J. Heckman and Anna L. Ziff's paper entitled